Mouse Model of Weak Depression Exhibiting Suppressed cAMP Signaling in the Amygdala, Lower Lipid Catabolism in Liver, and Correlated Gut Microbiota - Shimada, Kousuke; Nohara, Masakatsu; Yasuoka, Akihito; Kamei, Asuka; Shinozaki, Fumika; Kondo, Kaori; Inoue, Ryo; Kondo, Takashi; Abe, Keiko (Frontiers in Behavioral Neuroscience, 2022)
To establish a mouse model of weak depression, we raised six-week-old C57BL/6N mice in single (SH) or group housing (GH) conditions for two weeks. The SH group showed less social interaction with stranger mice, learning disability in behavioral tests, and lower plasma corticosterone level. The cecal microbiota of the SH group showed significant segregation from the GH group in principal coordinate analysis. Transcriptome analysis of the amygdala, and liver detected multiple differentially expressed genes (DEGs). In the amygdala of SH mice, suppression of the cyclic adenine monophosphate (cAMP) signal was predicted and confirmed by the reduced immunoreactivity of phosphorylated cAMP-responsive element binding protein. In the liver of SH mice, down-regulation of beta-oxidation was predicted. Interestingly, the expression levels of over 100 DEGs showed significant correlation with the occupancy of two bacterial genera, Lactobacillus (Lactobacillaceae) and Anaerostipes (Lachnospiraceae). These bacteria-correlated DEGs included JunB, the downstream component of cAMP signal in the amygdala, and carnitine palmitoyltransferase 1A, a key enzyme of beta-oxidation in the liver. This trans-omical analysis also suggested that NAD synthesis in the liver may be linked to the occupancy of Lactobacillus through the regulation of nicotinamide phosphoribosyltransferase and kynureninase genes. Our results suggested that SH condition along with the presence of correlated bacteria species causes weak depression phenotype in young mice and provide suitable model to study food ingredient that is able to cure weak depression.